Alisher Navoi's Image and the Issue of Artistic Interpretation - Ashurova, Gulbahor Ashurova (Researchparks Publishing, 2026)
Independence gave all the creators of our country the opportunity to think and create in a new way, to promote our high literary and aesthetic ideals, to show the historical truth truthfully, and to create works about great historical figures. The works of many writers were also portraying such developments in fiction. As is observed, the problem of historical fact and interpretation, as well as, the category of natural-aesthetic ideal, were studied by many foreign and Uzbek literary scholars and representatives of various branches of science. Their works touched the questions of the literary studies at various levels depending on the purposes and tasks they have set before them. The article is concerned with the Uzbek literature Great historical figures, light of the problem of historical fact and interpretation in the image of historical figures, the factors that led to the creation of a historical work, the evaluation of an artistic work. It also addresses the problem of attitude to the figures of historical literature in the Uzbek literature of the independence era, specifically, the problem of the atmosphereization of the figure of Navoi. Modern Uzbek literature investigates historicity and artistic interpretation of the image of a historical figure in art and this is the subject of the current article.